TANGGUNG GUGAT PERDATA TENAGA MEDIS TERHADAP KESELAMATAN PASIEN ( Studi kasus pada pelayanan radiologi ) - Anggraeni Endah Kusumaningrum (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
This paper discusses civil liability of medical personnel in radiology services to patient safety. Doctors as medical personnel in carrying out their duties must be accountable for the actions taken when providing health services to patients. The civil responsibility of the doctor is intended to prevent / avoid the things that are not desirable, also aims to obtain compensation for losses suffered by a patient. This civil liability is based on wanprestasi (article 1243 Civil Code) as well as unlawful acts /onrechtmatigedaad (article 1365 Civil Code), using the doctrine